Religion and Violence in Western Traditions: Selected Studies - Gagné, André (Routledge Studies in Religion Ser., 2021)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Contributors -- Introduction -- Note -- 1. "I will be an enemy to your enemies": the genocidal ideal in the Hebrew Bible and its legacy -- Introduction -- Enemy formation, identity, and violence in the Hebrew Bible -- Ḥerem as sacralized violence -- Ḥerem as genocide -- Ḥerem as eschatological violence -- The War Scroll (1QM) and the Jewish Wars with Rome -- Opposition to apocalyptic genocide within Judaism -- Conclusion -- Notes -- Bibliography -- 2. Turn the cheek but buy a sword: responding to violence in Luke-Acts -- Introduction -- Turning the other cheek -- A contrast in missions -- Staged fulfillment? -- The temptation to fight -- The presence of swords -- It is enough -- Jesus' arrest -- Jesus as Messiah in Luke-Acts -- Conclusion -- Notes -- Bibliography -- 3. Anabaptists and the apocalypse: the makings of a cosmic war in Münster -- Introduction -- The life and career of Melchior Hoffman, Herald of the apocalypse -- How the Melchiorites became Münsterites -- How the Münsterites became militants -- The siege of Münster as a cosmic war -- Conclusion -- Notes -- Bibliography -- 4. "Ruling [the Church] to its destruction and leading souls to hell in masses": violence, victimhood, and self-defence in the conciliarist discourse of Jacques Almain -- Introduction -- The organic analogy and ius to self-defence -- A biological body -- A political body -- The mystical body of Christ -- Papal violence against the whole Church -- The Church as a non-corporate collective -- Concern for the Church as the faithful -- Conclusion -- Notes -- Bibliography -- 5. Fearful symmetry: revelation, Hellboy, and pop apocalyptic violence -- Introduction -- Revelation's Christ/Antichrist complex -- Hellboy's Christ/Antichrist complex.